Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1029/2001jd000602
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ozone measurements from the Improved Limb Atmospheric Spectrometer

Abstract: Vertical profiles of ozone concentration in the high latitudes were observed by the Improved Limb Atmospheric Spectrometer (ILAS) aboard the Advanced Earth Observing Satellite (ADEOS) from November 1996 to June 1997. The ozone data obtained by the version 5.20 ILAS retrieval algorithm are compared with those obtained by the version 19 Halogen Occultation Experiment (HALOE), the version 6 Stratospheric Aerosol and Gas Experiment (SAGE) II, and the version 6 Polar Ozone and Aerosol Measurement (POAM) II retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 53 publications
(77 reference statements)
4
44
0
Order By: Relevance
“…Version 5.20 ILAS and version 1.4 ILAS-II ozone profiles were validated by comparing with various data sources (Sugita et al, 2002(Sugita et al, , 2006. These validations showed that ILAS ozone data agreed with other data sets within ±10 % with a few exceptions between 11 and 64 km (Table 1a, b).…”
Section: Ilas and Ilas-iimentioning
confidence: 85%
See 1 more Smart Citation
“…Version 5.20 ILAS and version 1.4 ILAS-II ozone profiles were validated by comparing with various data sources (Sugita et al, 2002(Sugita et al, , 2006. These validations showed that ILAS ozone data agreed with other data sets within ±10 % with a few exceptions between 11 and 64 km (Table 1a, b).…”
Section: Ilas and Ilas-iimentioning
confidence: 85%
“…The Improved Limb Atmospheric Spectrometer (ILAS) was a satellite-borne solar-occultation sensor on board the Japanese Advanced Earth Observing Satellite (ADEOS) (Sasano, 2002). ILAS consisted of an infrared spectrometer that covers the wavelength region from about 6 to 12 µm with a detector array of 44 elements and a visible spectrometer from 753 to 784 µm with a detector array of 1024 elements.…”
Section: Ilas and Ilas-iimentioning
confidence: 99%
“… Manney et al [2001] compared SAGE II, HALOE, and POAM II and III ozone data and found differences to be less than 0.5 ppmv (≈5%) in the upper stratosphere and ≈0.25 ppmv in the lower stratosphere. ILAS ozone is within 10% of HALOE, SAGE II, and POAM III between 20 and 50 km [ Sugita et al , 2002]. These data validation and comparison studies provide the justification for combining these data.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…The flexibility of the aircraft allows to investigate small and medium scale spatial variations in the stratosphere closing the gap between locally limited balloon measurements and synoptic satellite data. The high stability and reproducibility of the measurements performed with ASUR make this technique well suited for validation campaigns of spaceborne sensors as successfully done for UARS (MLS, HALOE) ATLAS (MAS), ERS-2 (GOME) and ADEOS (ILAS) (Crewell et al, 1995;Sugita et al, 2002;Kanzawa et al, 2003).…”
Section: The Asur Submillimeter Radiometermentioning
confidence: 99%
“…It is also apparent from Table 1 that in most cases in-situ instruments were used. Only very few examples of validation activities are reported in the literature where remote sensing instruments have been deployed on aircraft such as the NASA DC-8 , the DLR Falcon or the M55-Geophysika (Crewell et al, 1995;Englert et al, 2000;Feist et al, 2000;Schoeberl et al, 2002;Sugita et al, 2002;Kanzawa et al, 2003;Lumpe et al, 2003;Fix et al, 2003;Blom et al, 2003).…”
mentioning
confidence: 99%